Analysis of atmospheric air in the city of Kryvyi Rih and the contribution of motor vehicles to the pollution of the city - Halaktionov, Mykola; Hanoshenko, Olena (Academic journal Industrial Machine Building Civil Engineering, 2022)
Atmospheric air pollution is a significant problem of large cities, which leads to deterioration of the quality of life of the population. The city of Kryvyi Rih is characterized by a significant concentration of industrial facilities of the mining and metallurgical complex and motor vehicles, the combined effect of which causes technogenic stress on the environment. As a result of the study, it was established that the impact of motor vehicles on the atmospheric air of the city of Kryvyi Rih is increasing. An analysis of the impact of the city’s industrial facilities on the state of atmospheric air was carried out, and the contribution of motor vehicles to air pollution was determined. Areas with the most intense traffic were identified, where emissions from mobile sources were analyzed and recommendations were made to reduce the impact of these emissions